The colorectal cancer microenvironment: Preclinical progress in identifying targets for cancer therapy - Abdo Meyiah; Faez Iqbal Khan; Dia Aldeen Alfaki; Khaled Murshed; Afsheen Raza; Eyad Elkord (Translational Oncology)
Colorectal cancer (CRC) is a common cancer with high mortality rates. Despite progress in treatment, it remains an incurable disease for many patients. In CRC, the tumor microenvironment (TME) plays critical roles in tumor growth, progression, patients’ prognosis, and response to treatments. Understanding TME complexities is important for developing effective therapies. In vitro and in vivo preclinical models are critical in understanding the disease, discovering potential targets, and developing effective therapeutics. In this review, we focus on preclinical research studies associated with modulation of the TME in CRC. These models give insights into understanding the role of stroma and immune cell components of the TME in CRC and improve clinical responses, providing insights in novel treatment options. Various studies have focused on targeting the TME in CRC to improve responses to different therapeutic approaches. These include identifying targets for cancer therapies, targeting molecular signaling, and enhancing the efficacy of immunotherapeutic modalities. Furthermore, targeting stromal and angiogenic factors in the TME may provide new therapeutic options. Overall, understanding and targeting the TME in CRC is a promising approach for improving therapeutic outcomes.